PENGARUH AKUNTABILITAS DAN PENGENDALIAN INTERNAL KEUANGAN TERHADAP KINERJA PEGAWAI PADA BPKAD PROVINSI PAPUA BARAT - Dirk Swokabuy Urus; Maria Yertas; Mariana Salosso (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the partial and simultaneous effects of financial accountability and internal financial control on employee performance at the Regional Financial and Asset Management Agency (BPKAD) of West Papua Province. The research employed a quantitative descriptive-associative approach with multiple linear regression analysis. Data were collected from 47 civil servant respondents using proportionate stratified random sampling from a total population of 88 civil servants through Likert-scale questionnaires. Results indicate that: (1) financial accountability has a positive and significant effect on employee performance (β=0.487, t=4.623, sig=0.000), (2) internal financial control has a positive and significant effect on employee performance (β=0.341, t=3.218, sig=0.002), (3) simultaneously both variables significantly affect employee performance (F=47.832, sig=0.000) with R²=0.682, meaning 68.2% of the variation in employee performance is explained by financial accountability and internal financial control. Financial accountability is the more dominant variable. This study underscores the importance of strengthening accountability systems, improving Government Internal Control System (SPIP) effectiveness, and building a work culture oriented toward transparency and accountability to sustainably enhance BPKAD employee performance.